AKSI KOLEKTIF DI DUNIA DIGITAL: #ALLEYESONPAPUA DAN PERJUANGAN MASYARAKAT ADAT SUKU AWYU DAN MOI ATAS HUTAN ADAT - Ramadhanas , Faisal (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
On May 27, 2024, the indigenous Awyu and Moi sued the Supreme Court for the cancellation of an oil palm company's operational license, demanding the return of their exploited customary lands. This study analyzes the formation of collective action through social media to support the struggle for customary land rights, focusing on the use of the hashtag #AllEyesOnPapua as a mass mobilization tool and symbol of public solidarity. Through a collective action theory approach, this research explores the narratives on social media that create collective consciousness and trigger widespread public engagement. The results of the study are expected to show how social media opens up new spaces for solidarity actions in supporting the struggle of indigenous peoples against the exploitation of natural resources, while emphasizing the role of digital media in social advocacy.